The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.bbadis.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

TRPC6 and FSGS: The latest TRP channelopathy

Abstract: Focal and segmental glomerulosclerosis (FSGS) is a common cause of nephrotic syndrome in children and adults throughout the world. In the past 50 years, significant advances have been made in the identification and characterization of familial forms of nephrotic syndrome and FSGS. Resultant to these pursuits, several podocyte structural proteins such as nephrin, podocin, alpha-actinin 4 (ACTN4), and CD2-associated protein (CD2AP) have emerged to provide critical insight into the pathogenesis of hereditary neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 95 publications
1
58
0
Order By: Relevance
“…Myosin 1e (Myo1e) is one of the two Src homology 3 domain-containing "long-tailed" type I myosins in Actin filament cross-linking protein/Interacts with integrins and strengthens the podocyte-GBM interaction Atypical protein kinase C [68][69][70][71] Tight junctions/Formation of Par complex and interacts with slit diaphragm Rhophilin-1 [80] Rho GTPase activating protein 24 [80] Cytoplasm/Rho GTPase-interacting protein, integrity of glomerular filtration barrier Angiotensin II receptor [55][56][57] Angiotensin-converting enzyme [55][56][57] Membrane/pseudocyst formation at podocyte CD2-associated protein [65][66][67] CD2-associated protein [64] Insertion site of the slit diaphragm/Formation SD complex with podocin and nephrin Laminin subunit beta-2 [81][82][83][84] Laminin subunit beta-2 [81][82][83][84] Podocyte anchoring and differentiation in GBM microRNA 193α [74,75] Cytoplasm/Inhibition of expression of WT-1 Myosin 1e [49,50] Myosin 1e [49,50] Actin binding long-tailed motor protein/Regulation of actin cytoskeleton Nuclear factor of activated T cells [76,77] Transient receptor potential 6 [53,54] Membrane/the activation of calcineurin-NFAT/Wnt signaling via the increased calcium influx Podocin [46] Podocin [58,59] Insertion site of the SD/SD assembly and maintaining the signaling of nephrin Shroom family member 3 …”
Section: Myosin 1e Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Myosin 1e (Myo1e) is one of the two Src homology 3 domain-containing "long-tailed" type I myosins in Actin filament cross-linking protein/Interacts with integrins and strengthens the podocyte-GBM interaction Atypical protein kinase C [68][69][70][71] Tight junctions/Formation of Par complex and interacts with slit diaphragm Rhophilin-1 [80] Rho GTPase activating protein 24 [80] Cytoplasm/Rho GTPase-interacting protein, integrity of glomerular filtration barrier Angiotensin II receptor [55][56][57] Angiotensin-converting enzyme [55][56][57] Membrane/pseudocyst formation at podocyte CD2-associated protein [65][66][67] CD2-associated protein [64] Insertion site of the slit diaphragm/Formation SD complex with podocin and nephrin Laminin subunit beta-2 [81][82][83][84] Laminin subunit beta-2 [81][82][83][84] Podocyte anchoring and differentiation in GBM microRNA 193α [74,75] Cytoplasm/Inhibition of expression of WT-1 Myosin 1e [49,50] Myosin 1e [49,50] Actin binding long-tailed motor protein/Regulation of actin cytoskeleton Nuclear factor of activated T cells [76,77] Transient receptor potential 6 [53,54] Membrane/the activation of calcineurin-NFAT/Wnt signaling via the increased calcium influx Podocin [46] Podocin [58,59] Insertion site of the SD/SD assembly and maintaining the signaling of nephrin Shroom family member 3 …”
Section: Myosin 1e Modelmentioning
confidence: 99%
“…This mutation leads to a gain of function and a transient increase of intracellular calcium concentration [53]. Krall et al described the generation and phenotypic characterization of three different transgenic mice lines with podocyte-specific overexpression of the wild type or any of two mutant forms of Trpc6 (P111Q and E896K) previously related to FSGS.…”
Section: Transient Receptor Potential Channel 6 Modelmentioning
confidence: 99%
“…Apoptosis-stimulating Ca 2þ channels or unselective cation channels include NMDA receptors [73], purinergic receptors [74,75], as well as the TRP channels [76] TRPC1 [77], TRPC3 [78], TRPC6 [79][80][81] In glioma cells, TRPC1 is required for cytokinesis in proliferation and migration [95,96]. Ca 2þ entry through TRPM8 channels leads to the activation of Ca 2þ -sensitive K þ channels (KCa1.1), which participate in the machinery accomplishing migration [5,97].…”
Section: Ca 2þ Permeable Cation Channelsmentioning
confidence: 99%
“…In addition, these gene mutations have been shown to be associated with a reduced incidence of relapse of proteinuria upon renal transplantation (13). One of these proteinuria candidate genes, canonical transient receptor potential channel 6 (TRPC6), encodes TRPC6 protein, a Ca 2+ -permeable nonselective cation channel, which is a member of the transient receptor potential channel subfamily (10). In 2005, Winn et al first identified TRPC6 variants segregated with the development of familial FSGS.…”
mentioning
confidence: 99%
“…These proteins have been proven essential for the signaling initiated from the slit diaphragm, which is the key component of the glomerular filtration barrier (10). Therefore, these mutations may contribute to disrupted filtration function and increased protein permeability.…”
mentioning
confidence: 99%